Very first questions and answers what are clouds? - Daynes, Katie; Harrison, Suzie; Miguens, Marta Alvarez (London Usborne house, 2021)
Discover what clouds are made of, why storm clouds flash and boom, how tornadoes happen and what makes a rainbow. With lots of flaps to lift, this delightful book encourages children to explore clouds for themselves, spotting shapes in the sky, looking at the simple science behind them and learning a few cloud myths along the way
Scientific notions
Keywords: Science